Implementation of the "Lauk Murik" Teaching Material in Science Lessons for Fifth Grade Students of State Elementary Schools 1 Kuluk Talawang - Bulkani, Bulkani; Elhawwa, Tazkiyatunnafs; Weni, Fitri (Reflection Journal, 2026)
In harmony with an environment rich in local wisdom, the environment also needs to be utilized as a source and medium for learning, because the learning process involves seeing, observing, and experiencing, so that students can understand things that exist in real life. The changing educational paradigm demands the use of teaching materials that are contextual, meaningful, and relevant to students' lives. This study aims to describe the implementation of the local teaching material "Lauk Murik" in Natural and Social Sciences (IPAS) learning for fifth-grade students at SD Negeri 1 Kuluk Talawang. The use of this teaching material was developed as an effort to integrate the local cultural context into learning, thereby increasing student engagement and strengthening conceptual understanding. The subject of this reserach was 31 students with 16 male and 15 female. The study used a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results indicate that the "Lauk Murik" teaching material can enhance learning activities, facilitating students' understanding of IPAS concepts related to food, natural resources, and environmental sustainability. Furthermore, the integration of local cultural values ​​makes learning more relevant and meaningful. This study recommends the further development of local wisdom-based teaching materials in the IPAS subject in elementary schools